The Role of Tourism in the Sustainable Development Goals - Fadliyanti, Luluk; Harsono, Iwan; Sutanto, Himawan; Handayani, Tuti; Arkandia, Lalu Dema; Jalaludin, Jalaludin (Penelitian dan Pengembangan Ilmu, 2024)
Tourism plays a crucial role in sustainable development, particularly in developing countries. This study aims to explore the relationship between the implementation of sustainable tourism practices and the contribution of the tourism sector to achieving Sustainable Development Goals (SDGs) in developing countries. The research utilizes a systematic literature review approach to analyze existing literature on the topic. Indicators for sustainable tourism practices and the contribution of the tourism sector to SDGs are identified. The study hypothesizes that greater implementation of sustainable tourism practices leads to a higher contribution of the tourism sector to achieving SDGs. Findings suggest that sustainable tourism practices, including environmental sustainability, community participation, and policy alignment with SDGs, are positively associated with the tourism sector's contribution to sustainable development. This study contributes to the understanding of how sustainable tourism practices can enhance the tourism sector's role in achieving SDGs in developing countries.